A Framework to Understand Effect of Building Systems Deterioration on Life Cycle Energy. (2015) - Thomas, Albert; Menassa, Carol C.; Kamat, Vineet R.
Abstract: The building sector accounts for nearly 41% of U.S. primary energy use. Various tools have been developed for estimating the embodied energy during the design and construction phase of a building. However, there is a lack of a comprehensive mechanism which can measure and control the energy flow occurring during the operation phase of a building. Loss of efficiency of building systems and deterioration of various building components can collectively reduce the performance of a building, which eventually results in more energy flow into a building in the form of more maintenance and replacement requirements, as well as, increased operational energy demand. This research analyses a building's deterioration mechanism and presents a system dynamics simulation based "Life Cycle Energy Framework" that couples material performance and energy simulation to arrive at an optimal maintenance and replacement cycle for major materials over the entire operation period of a building. The case study results indicate that the proposed framework can help various building stakeholders in understanding and limiting the energy usage of the building from the design phase until the end of life phase.